How changing organizational culture can enhance innovation: Development of the innovative culture enhancement framework - Salaheddine Bendak; Amir Moued Shikhli; Refaat H. Abdel-Razek (Cogent Business & Management, 2020)
Innovation is considered one of the key factors that influence long-term success of any organization. The published literature indicates that establishing and enhancing the right culture that supports innovation in the organization is a precondition for innovation. The objective of this study is to propose and validate a framework, called the Innovative Culture Enhancement Framework (ICEF), which can be used to enhance innovation at any given organization based on its culture. First step in the framework involves using the Organizational Culture Assessment Instrument (OCAI) to determine the level of each culture type within the organization. Then, the Community Innovation Survey (CIS) is used to determine the level of each innovation type. The third step of ICEF involves doing multiple linear regression analyses of OCAI outcomes over CIS results to determine how each culture type contributes to each innovation type. The fourth step involves comparing existing level of each innovation type with the desired level as indicated by the management. The fifth and last step involves adjusting existing level of culture types in a way that enhances the desired innovation type. ICEF was validated by implementing it at three medium-size companies and was found to be workable and giving statistically significant outcomes. Then, the framework was further validated by interviewing a group of industry experts and seeking their opinion on ICEF dimensions. Statistical analysis of the interviews mainly gave high item-to-total correlations for the dimensions explored and a high Cronbach's alpha value leading to conclude that the framework is reliable and delivers what it was developed for. It is recommended that future research explores further how culture can be used as a driving force for innovation in organizations.
Keywords: 650; organizational culture; organizational innovation; framework; competitiveness